2015
DOI: 10.1177/0023830914564452
|View full text |Cite
|
Sign up to set email alerts
|

Asking or Telling – Real-time Processing of Prosodically Distinguished Questions and Statements

Abstract: We introduce a targeted language game approach using the visual world, eye-movement paradigm to assess when and how certain intonational contours affect the interpretation of utterances. We created a computer-based card game in which elliptical utterances such as "Got a candy" occurred with a nuclear contour most consistent with a yes-no question (H* H-H%) or a statement (L* L-L%). In Experiment I we explored how such contours are integrated online. In Experiment 2 we studied the expectations listeners have fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…After the end of the Object constituent (where the nucleus was located), fixations on the target picture exhibited a sharp increase. This is in line with a previous study in American English, which have shown immediate use of the nuclear accents and boundary tones for processing questioning vs. asserting utterances [16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…After the end of the Object constituent (where the nucleus was located), fixations on the target picture exhibited a sharp increase. This is in line with a previous study in American English, which have shown immediate use of the nuclear accents and boundary tones for processing questioning vs. asserting utterances [16].…”
Section: Discussionsupporting
confidence: 93%
“…The present study used an eye-tracking task to test listeners' online responses to prenuclear contour. Studies have reported an anticipatory effect of prosodic prominence [15] and the effect of boundary tones to elicit assertions vs. yes/no questions judgments [16]. However, the stimuli of [16] were limited to less typical syntactic constructions of American English (elliptical utterances only containing the nucleus).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the terminal cues that distinguish declarative questions from statements, pre-terminal cues and nonmelodic prosodic cues, which vary across languages, are also available (Face, 2005;Fal e and Faria, 2006;Heeren et al, 2015;Haan, 2000, 2002;Van Heuven and Van Zanten, 2005;Vion and Colas, 2006). In fact, a gating task with word-length increments revealed that pre-terminal cues enable English-speaking adults to differentiate naturally produced declarative questions from statements after hearing the first word (Saindon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Online processing of intonation in contrastively focused elements has been studied mainly in stress-accent languages such as English or German, revealing that speakers use pitch accent location and pitch accent type to create online expectations about an upcoming referent [7]- [12]. In [9], participants first heard a sentence like "Put the candy/candle below the triangle" and then a sentence like "Now put the candle above the square", where 'candle' could either be accented or deaccented.…”
Section: Introductionmentioning
confidence: 99%